An Integrated Intelligent Building System with Remote Control - Leszek KACHEL; Sylwester SIMIŃSKI (Communications of International Proceedings, 2021)
This article describes the possibilities of adapting an existing building or apartment based on traditional and independent subsystems to an intelligent building. The solutions that can be implemented have been described, through the use of systems and devices available on the market, in order to integrate: heating, ventilation, air-conditioning and lighting systems, as well as enabling remote control and monitoring actual state of devices.
Keywords: Smart Home; intelligent building; building automation; building installation